Kajian Proses Pengolahan Tembikar untuk Pembuatan Fasilitas Duduk di Pottery 66 Denpasar - Eman, Monica Naomi; Darmayanti, Tessa Eka; Jonatan, Lisa Levina Kisanti (Ideas Publishing, 2024)
Pottery, a type of clay with high elasticity that turns to hard surfaces after firing, has been an integral part of the lives of Indonesian people since the time of their ancestors. Pottery products such as jars, tableware, roof tiles, floor tiles, and others have supported everyday life. Bali is known as one of the pottery centres in Indonesia, but its presence is threatened due to the lack of interest and efforts of the younger generation to develop knowledge about pottery. Pottery 66, as a seller in Denpasar, has succeeded in penetrating the export market and is the only workshop that makes seating facilities made from pottery, unique to Pottery 66. Pottery 66 has succeeded in developing pottery in the interior sector, especially seating facilities which are the focus of this study. This research was conducted to find out the entire process of making chairs from pottery at Pottery 66 as well as to obtain specifications for making chairs from pottery at Pottery 66 and also to find out the size limits that can be achieved from pottery materials in interiors which can be a guide for further development by Pottery 66. The objectives of this research will be achieved using qualitative methods through observation, direct surveys of the Pottery 66 workshop, interviews with project leaders, and documentation. Through this study, it is hoped that it can create space for young designers to develop in exploring pottery materials and will then help arouse the interest of the younger generation in pottery, to prevent the extinction of the pottery industry, especially in the city of Bali which is rich in arts and crafts traditions